Influence of the regional topography on the remote emplacement of hydrothermal systems with examples of Ticsani and Ubinas volcanoes, Southern Peru - Byrdina, Svetlana (2013)
Present work studies the influence of the regional topography on the hydrothermal fluid flow pattern in the subsurface of a volcanic complex. We discuss how the advective transfer of heat from a magmatic source is controlled by the regional topography for different values of the averaged permeability. For this purpose, we use a 2-D numerical model of coupled mass and heat transport and new data sets acquired at Ticsani and Ubinas, two andesitic volcanoes in Southern Peru which have typical topography, justifying this approach. A remarkable feature of these hydrothermal systems is their remote position not centered on the top of the edifice. It is evidenced by numerous hot springs located in more than 10 km distance from the top of each edifice. Upwelling of thermal water is also inferred from a positive self-potential anomaly at the summit of the both volcanoes, and by ground temperatures up to 37 °C observed at Ticsani. Our model results suggest that the regional topographic gradient is able to significantly divert the thermal water flow and can lead to an asymmetric emplacement of the hydrothermal system even considering a homogeneous permeability of the edifice. Inside the thermal flow, the hydraulic conductivity increases with the decrease of temperature-related viscosity, focusing the flow towards the surface and creating a hydrothermal zone at a large lateral distance from the heat source. The location and temperature of the hot springs together with the water table position given by self-potential data can be used to constrain the average permeability of the edifice, a key parameter influencing fluid flow and associated advective heat transfer in the direction opposite to the regional topographic gradient. Our study allows to explain the emplacement of the hydrothermal systems at volcanoes with asymmetric edifices or even the absence of a shallow hydrothermal system. These results can be generalized to the study of non-volcanic hydrothermal systems.